Agency-linked risk management with ownership and board sub-committee governance: Evidence from an OECD economy - Omar Al Farooque (Journal of Risk and Financial Management, 2021)
From a risk management perspective, this study examines the role of ownership and board sub-committee governance on direct measures of agency costs in a small OECD economy - New Zealand. Using Logistic and OLS regression approaches, two proxies of direct agency costs are tested on a pooled sample of 466 firm-year observations ranging from 2012 to 2018. The study provides evidence that insider ownership concentration outperforms outsider ownership concentration in constraining agency costs. Moreover, audit committee independence can also effectively deter agency costs. These findings suggest that both insider ownership concentration and audit committee structure are important risk management mitigating factor for deterring agency costs in New Zealand companies.
Keywords: 330; board sub-committee structure; direct measures of agency costs; New Zealand; ownership concentration; risk management